Influence of trunk strength on sprint performance in swimmers: a cross-sectional analysis of torque-velocity relationships - Dai, Jinjin; Dai, Zicheng; Ding, Yahui (Frontiers in Physiology, 2025)
This cross-sectional study assessed trunk strength at 60°/s and 120°/s angular velocities in swimmers and its relationship to 100-m sprint performance. Thirty-two elite swimmers (age: 19.49 ± 1.44 years; height: 177.77 ± 6.84 cm; body mass: 71.88 ± 8.50 kg) underwent isokinetic trunk testing and timed sprints. All tests demonstrated excellent reliability (ICC >0.96). Swimmers had significantly greater peak torque in extension compared to flexion (p < 0.01), and higher torque in left versus right rotation, though the latter was not significant. Contrary to the hypotheses, peak torque at 120°/s did not correlate more strongly with performance than at 60°/s, and rotation torque did not surpass flexion/extension metrics. After Benjamini–Hochberg FDR correction for 24 comparisons, no significant correlations remained (q < 0.05), indicating initial associations were likely confounded by sex differences. These results suggest training should emphasize inter-segmental coordination over isolated strength gains, focusing on torque transfer from trunk to extremities. Interpretation of high-velocity torque data requires caution due to potential acceleration artifacts at early peak angles (5°–7°).